The localization of the bullous pemphigoid and cicatricial pemphigoid antigens: direct and indirect immunofluorescence of suction blisters. - Venning, V; Allen, J; Millard, P; Wojnarowska, F (1989)
The location of in vivo bound immunoreactants was studied in 37 patients with subepidermal blistering diseases by direct immunofluorescence (IMF) on suction blisters taken from uninvolved forearm skin. The patients studied included 18 with bullous pemphigoid (BP), nine with cicatricial pemphigoid (CP), three with acquired epidermolysis bullosa (EBA) and 7 hybrid cases. The patterns of IMF in the suction blisters were: BP, epidermal 1, dermal 1, combined 4, negative 12; CP, epidermal 1, dermal 2, negative 6; EBA, dermal 2, negative 1; and 'hybrid' patients, epidermal 3, negative 4. The different patterns of suction blister staining could not be correlated with the clinical features of the patients in respect of mucous membrane involvement, scars or milia or a history of skin fragility. Both BP and CP are probably heterogeneous in respect of their antigen specificity, and the two diseases cannot reliably be distinguished by the patterns of direct IMF on suction blisters. In addition, some individual patients with BP have more than one target antigen as indicated by a combined pattern of suction blister fluorescence. The lack of correlation between the pattern of suction blister fluorescence and the clinical features suggests that factors other than antigen specificity determine the clinical expression of subepidermal blistering diseases.